PENGARUH MOTIVASI KERJA DAN PERILAKU KEPEMIMPINAN TERHADAP KINERJA PEGAWAI - Hidayat Hidayat; Adnan Hakim; Juharsah Juharsah; Yusuf Montundu; Hastuti Hastuti; Moh. Amin (Jurnal Manajemen, Bisnis dan Organisasi (JUMBO), 2020)
This study aims to determine the simultaneous and partial influence of work motivation and leadership behavior on employee performance. The population of this study was all 88 employees of the Southeast Sulawesi Provincial Inspectorate Office and all of them were sampled. Data was collected using questionnaire and interview instruments. Data were then analyzed by multiple linear regression analysis. The analysis shows that work motivation and leadership behavior simultaneously and partially affect employee performance.